THEORETICAL FOUNDATIONS OF STUDYING CHILDREN’S GAMES IN ENGLISH AND UZBEK FAIRY TALES - Muhammadjonova Ma'muraxon Muhsinjon qizi; Otabek Mukhamadovich Fayzulloyev. (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the theoretical foundations of studying children’s games in English and Uzbek fairy tales. It examines the role of play as a cultural and pedagogical phenomenon reflected in folklore and analyzes how games function as symbolic elements within narratives. The study highlights the educational, moral, and social values transmitted through children’s games and their significance in shaping cultural identity across generations. By comparing English and Uzbek traditions, the article provides insights into both universal and culture-specific aspects of play in folklore, offering a deeper understanding of how fairy tales integrate entertainment with moral and educational purposes.